2022
DOI: 10.3390/tomography8060230
|View full text |Cite
|
Sign up to set email alerts
|

Biatrial Volumetric Assessment by Non-ECG-Gated CT Pulmonary Angiography Correlated with Transthoracic Echocardiography in Patients with Normal Diastology

Abstract: Atrial size is a predictor of cardiovascular mortality. Non-ECG-gated computed tomography pulmonary angiography (CTPA) is a common test for cardiopulmonary evaluation but normative values for biatrial volumes are lacking. We derived normal CT biatrial volumes using manual and semiautomated segmentation with contemporaneous transthoracic echocardiography (TTE) to confirm normal diastology. Thirty-five consecutive cases in sinus rhythm with no history of cardio-vascular, renal, or pulmonary disease and normal di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Although measurement is more accurate using ECG-gated CT, clinical CT for lung tumors is usually performed without ECG gating. A recent study 37 has shown that non-ECG gated CT is a reliable method for measuring left and right atrial volumes in patients with normal atrial function, and is comparable to transthoracic echocardiography in terms of accuracy and reproducibility. Additionally, non-ECG gated CT can identify cases of LA enlargement with high specificity (94%) 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Although measurement is more accurate using ECG-gated CT, clinical CT for lung tumors is usually performed without ECG gating. A recent study 37 has shown that non-ECG gated CT is a reliable method for measuring left and right atrial volumes in patients with normal atrial function, and is comparable to transthoracic echocardiography in terms of accuracy and reproducibility. Additionally, non-ECG gated CT can identify cases of LA enlargement with high specificity (94%) 38 .…”
Section: Discussionmentioning
confidence: 99%